FACTORS INFLUENCING MAKERS IN LONG ACTING REVERSIBLE CONTRACEPTIVES IN BAJAWA SUB DISTRICT - Agustina Yasinta Yami; Gadis Meinar Sari; Atika Atika (UNIVERSITAS AIRLANGGA, 2020)
ABSTRACTLong-Acting Reversible Contraceptives (LARCs) is a contraceptive method recommended by the government which has long-term protection and high effectiveness with a failure rate of 0.5 to 2 pregnancies / 100 women in the first year of usage. The use of LARCs are influencing by the role of health officers and decision-makers. This study aimed to analyze relationship between the role of health officers and decision-makers with the use of LARCs. Methode used is an observational analytic study using a cross-sectional approach. with 92 samples respondents. The technique used in sampling was consecutive sampling. The independent variables were the role of health officer and decision-makers while , the dependent variable was LARCs usage. The bivariate analysis test used the chi-square test and fisher’s exact. The Result shows the most common of contraceptive usage was non-LARCs. The results of chi-square analysis showed p-value <0.05 stated statistically associated between the role of health officers and LARCs usage (0.017). In contrast, the result of fisher’s exact analysis showed p-value > 0,05 stated non statistically associated between decision makers and LARCs usage (0,793). Conclusions: Concluded that the role of health officers associated with LARCs while decision makers aren’t associated with LARCs usage.